Barriers to effective communication in Petronas Dagangan Berhad (PDB) / Nur Khalisah Muhammed Zulfikri - Muhammed Zulfikri, Nur Khalisah (Faculty of Business and Management, 2019)
Communication effectiveness has been one of important factors in daily life covering workplaces, relationships, and all sorts of human interaction. As a workplace or even learning Centre’s, any organization shall need to practice good and effective communication from within and out to achieve its goals. Many researchers have developed and shared various theories, models and frameworks with regards to this topic of interest due to its crucially to be achieved and practiced. However, communication is a very broad subject and is affected by many internal and external factors. The internal and external factors may both refers to communication barriers, which could be a stimulus, a situation or even an object that may hinder or prohibit any part of a communication process making it harder for messages to be encoded and decoded precisely by parties involved. The purpose of this research is to investigate the factors influencing effective communication in an organization. This research is a qualitative research that used questionnaires as the instrument for the collection of data. The data was collected and viable at 77% out of 69 respondents which was derived from the total population of 90 elements. Sample selection was based on a non-probability approach. The data collected was then evaluated by using Statistical Package for the Social Science (SPSS) through which numerous tests were converged such as reliability test, normality test, frequency distribution, descriptive analysis and multiple regression analysis. The results indicated that environmental barrier is more related to effective communication than language and culture.